2019
DOI: 10.1186/s13075-019-1832-z
|View full text |Cite
|
Sign up to set email alerts
|

Resetting the clock on arthritis

Abstract: While many of intricacies of the mammalian circadian rhythm remain unknown, the role that this physiological clock plays in our everyday lives and within the global ecosystem is clearly evident. However, only recently has the importance of circadian rhythm in cartilage health and joint homeostasis been brought to light. A recent study by Hand and colleagues advances our understanding of these processes further by demonstrating that disruption of circadian clock regulation in mesenchymal cells not only has an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Previous findings from our group and others have shown that the circadian clock is disrupted in human OA () and that perturbation of the circadian clock promotes OA pathogenesis (). Furthermore, FoxO pathways are disrupted in OA (1) and have been linked to circadian rhythms ().…”
Section: Discussionmentioning
confidence: 75%
“…Previous findings from our group and others have shown that the circadian clock is disrupted in human OA () and that perturbation of the circadian clock promotes OA pathogenesis (). Furthermore, FoxO pathways are disrupted in OA (1) and have been linked to circadian rhythms ().…”
Section: Discussionmentioning
confidence: 75%